Some Results for the Drazin Inverses of the Sum of Two Matrices and Some Block Matrices - Abdul Shakoor; Hu Yang; Ilyas Ali (Journal of Applied Mathematics)
We give a formula of (P+Q)D under the conditions P2Q+QPQ=0, P3Q=0, and PQPQ=0. Then, we apply it to give some expressions for the Drazin inverse of block matrix M=(ABCD) (A and D are square matrices) under some conditions, generalizing some recent results in the literature. Finally, numerical examples are given to illustrate our results.